Applied physical geography: GE Hollis, Man's Impact on the Hydrological Cycle in the United Kingdom, Geo Abstracts: Norwich, 1979, 278 pages. (February 2015) - Watts, Glenn
In the papers collected in Man's Impact on the Hydrological Cycle in the United Kingdom Hollis gives us a fascinating view of the concerns and approaches of practising hydrologists in the late 1970s. Hollis, a physical geographer from University College London, spent most of his research career considering the way that humans acted to change their surroundings, looking first at the impact of urbanisation on flooding and later at the management of wetlands. The papers in this book cover a wide range of subjects, from the impact of forestry to the effects of house building on channel morphology and function. Many provide valuable reviews and insights into contemporary thinking on the effect of humans on the UK environment, and the modern reader will discover much of value in the ideas and approaches described in this book.